Dietary fenugreek (Trigonella foenum-graecum) seeds and garlic (Allium sativum) alleviates oxidative stress in experimental myocardial infarction - P. Mukthamba; K. Srinivasan (Food Science and Human Wellness)
Soluble fiber-rich fenugreek seeds (Trigonella foenum-graecum) and garlic (Allium sativum) are understood to exert cholesterol-lowering and antioxidant effects. The cardioprotective influence of a combination of fenugreek seeds and garlic by their antioxidant influence was evaluated in hypercholesterolemic rats administered isoproterenol. Wistar rats were maintained on high-cholesterol diet for 8 weeks along with dietary interventions of fenugreek (10%), garlic (2%) and their combination. Myocardial infarction was induced with isoproterenol injection. Increased circulatory troponin, disturbed activities of cardiac ATPases, increased serum iron and decreased ceruloplasmin confirmed myocardial infarction. Elevated lipid peroxides accompanied with reduced antioxidant molecules caused by isoproterenol and altered activities of antioxidant enzymes in serum and heart in induced myocardial necrosis were countered by dietary fenugreek, garlic, and fenugreek + garlic. Dietary fenugreek seeds and garlic ameliorated isoproterenol-induced compromised antioxidant status, the cardioprotective effect being higher by the combination of fenugreek seeds and garlic.